Perjanjian Kredit pada Bank Perkreditan Rakyat - Ashadi L Diab (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
An agreement is a legal relation of property between two parties, while the other party has the right to demand its implementation. In order for the agreement to have the force of law, it must meet the requirements of the validity of the agreement contained in article 1320 of the Civil Code. One of the most important things in the credit agreement of the bank is the guarantee for the lending party or the bank (Creditor) guarantee in relation to the credit is one of the conditions for the grant of credit application. The guarantee here is not only the property of the debtor, but also can be an immaterial guarantee. In forming credit there needs to be a guarantee, so there is certainty that the credit given to the debtor can be accepted again in accordance with the conditions that have been determined. Guarantee commonly used by BPR